EcosystemPesantrenpreneurshipin Realizing Teacher Welfare and Student Potential Through Islamic Education-Based Cooperative Entrepreneurship - Heryandi, M Tubi; Indah Doktri Agus Tapaningsih, Weni; Hosaini, Hosaini (Maharot : Journal of Islamic Education, 2025)
slamic boarding schools (pesantren) are not only centers of religious education but also hold significant potential as drivers of community-based economic development. Ann-Nuqo' Islamic Boarding School in Taman Village, Bondowoso Regency, is one Islamic educational institution striving to develop economic independence, despite still facing challenges related to teacher welfare and the utilization of student potential. The objective of this research is to formulate a model for an Islamic boarding school entrepreneurship ecosystem by strengthening cooperatives as a means of entrepreneurial learning and a source of additional income.The research method used was descriptive qualitative, using participatory observation, in-depth interviews, and documentation studies. The collected data was analyzed thematically to identify economic empowerment strategies tailored to local characteristics.Research shows that limited access to economic resources and a lack of entrepreneurial skills are the main obstacles facing Islamic boarding schools. However, Islamic boarding school cooperatives have significant potential to become economic drivers if managed in an inclusive and participatory manner. Developing training programs based on local potential, such as organic farming, handicrafts, and digital marketing, can increase the capacity of students and expand economic benefits for the surrounding community.The conclusion of this study emphasizes the importance of pesantrenpreneurship as a strategic solution to support the independence of Islamic boarding schools. The implication is that Islamic boarding schools can transform into centers of sustainable economic growth, while simultaneously strengthening their educational function by equipping students with practical skills relevant to the needs of the times